2010
DOI: 10.1017/s1041610210000694
|View full text |Cite
|
Sign up to set email alerts
|

Peaceful mind: an open trial of cognitive-behavioral therapy for anxiety in persons with dementia

Abstract: Background Anxiety has a high prevalence among individuals with dementia, and it has a significant negative impact on their functioning; yet intervention studies are lacking. We developed Peaceful Mind, a cognitive-behavioral intervention for persons with dementia. In this article, we describe the intervention and results of an open trial evaluating the feasibility and utility of the intervention and assessment procedures. Methods Peaceful Mind is implemented over a period of 3 months in the participant's ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 26 publications
0
72
0
Order By: Relevance
“…Using a more lenient method for assessing change (i.e. a 20% reduction in scores on depression and anxiety scales from baseline), Paukert et al (2010) showed only a modest level of improvement. According to Paukert et al (2010), 75% of participants showed an improvement in depression at three months and 57% at six months, and 25% of participants showed improvement in anxiety at three months and 57% at six months.…”
Section: O G N I T I V E B E H a V I O R T H E R A P Ymentioning
confidence: 99%
“…Using a more lenient method for assessing change (i.e. a 20% reduction in scores on depression and anxiety scales from baseline), Paukert et al (2010) showed only a modest level of improvement. According to Paukert et al (2010), 75% of participants showed an improvement in depression at three months and 57% at six months, and 25% of participants showed improvement in anxiety at three months and 57% at six months.…”
Section: O G N I T I V E B E H a V I O R T H E R A P Ymentioning
confidence: 99%
“…Calleo et al [19] reported that 43% of the patients with AD and anxiety who had a Neuropsychiatric Inventory score for anxiety of more than 4 points met the criteria for GAD. Some reports indicated that treatments for anxiety disorder, including short-acting benzodiazepine or cognitive behavioral therapy, were also effective for the treatment of anxiety in AD [20,21,22]. However, a consensus on how to define anxiety in dementia, including AD, has not yet been achieved [16].…”
Section: Introductionmentioning
confidence: 99%
“…6062 CBT skills such as diaphragmatic breathing and coping statements were implemented in two case studies conducted by Kraus and colleagues (61). Skills were simplified in order to address comprehension, learning, memory and application issues that may arise when working with PwD.…”
Section: Case Study—partmentioning
confidence: 99%